The use of assistance flow by nurses to the patient with chest pain: facilities and difficulties - Valesca Mônica Rodrigues Lima; Maria dos Milagres Farias da Silva; Irialda Saboia Carvalho; Cleide Carneiro; Ana Patrícia Pereira Morais; Geanne Maria Costa Torres; Antonio Germane Alves Pinto
ABSTRACT Objective: to analyze the facilities and difficulties in the use by nurses of the care flow for patients with chest pain. Methods: descriptive analytical study, with a qualitative approach, conducted with 17 nurses from an emergency care unit in a municipality of the State of Ceara, in 2018. Data collected through documents and interviews, analyzed in a descriptive manner, in absolute and relative frequencies and through content analysis thematic. Results: the use of assistance flow streamlines the process of transferring to referral units, reducing serious and lethal complications in the patient. It considers teamwork and communication as facilitating points in the care of patients with chest pain. The lack of permanent education, physical structure, equipment, transport delay and patient regulation as factors that hamper. Final considerations: investments in physical structure and equipment, in the reorganization of the care network and in permanent education to enable benefits to the service of excellence in health care.